(untitled) (Brazilian Journal of Radiation Sciences (BJRS), 2021)
Iodine is one of the essential trace elements of much interest in nutritional research being responsible for the production of the thyroid hormones, which has great importance for human metabolism. Edible algae species accumulate iodine from seawater and are considered a good dietary source of this nutrient. The Epithermal Neutron Activation Analysis (ENAA) was applied to determine the iodine concentration in edible algae species and derivatives. Twenty-one samples for 4 edible algae species Porphyra umbilicalis (common name: Nori), Hijikia fusiforme (Hijiki), Undaria pinnatifida (Wakame) and Laminaria spp. (Kombu) and 3 samples of the derivative sample, ágar, were analyzed. The results pointed out a great variability of I concentration in these species. The highest I concentration obtained was 9324±113 mg/kg in Laminaria spp. (Kombu). Hijikia fulsiforme (Hijiki) also presented high values (1803±86 mg/kg). The lowest I content was obtained in agar samples (3.18±0.29 mg/kg). All analyzed algae samples exceed the recommended value (150 µg/day) and an ingestion of 1 g/day of Laminaria spp. (Kombu) exceed the maximum tolerable limit (1100 μg/day) and its consumption must be controlled to avoid possible health problems.